Concepções de trabalho e profissionalização docente: sua redução à ação empreendedora - Raimann, Elizabeth Gottschalg (2015)
The teaching work is a field of competition and contradictions. If on the one hand, there is an effort to the teachers training and valorization, on the other hand, there is an ongoing process of disqualification, de-professionalization and devaluation of their work, under the entrepreneurial discourse that suggests autonomy, innovation and good performance. This research, a documental research type, aimed at answering the following questions: What conceptions of work and professionalization are present in official documents? For what and for whom is the teacher professionalization necessary? In what way is entrepreneurship presented, and how does it affect the teaching? The research is justified since, while questioning the national policy of valorization concerning on Magisterium for basic Education, implemented by the Federal Government between 2003-2010, this points to a new professional profile. The theoretical-methodological procedure took up contributions of Critical Discourse Analysis (CDA) subsidized by the reference of dialectical historical materialism (MHD), which are important for analyzing the work categories, the teacher professionalism, and entrepreneurship. Considering the documents for analysis, in the legal plan, it was taken into consideration the speeches from both international and national organizations, such as :UNESCO, Federal Government, National Confederation of Workers in Education, National Education Council; at the government plan, the discourse of the propositions, programs and interviews from those who represent the government; on the civil society plan, the speeches on work teaching, the teacher professionalization, and entrepreneurship which is present in printed and online media, in scientific and opinion articles , interviews, and surveys as well. As a result, although the documents point to the development and professionalization, the research uncovered conflicts between what education professionals advocate and what the federal government interprets as work and professionalization; the objective and subjective teaching conditions point straight to the teaching de-professionalization. The management principle by results, in which the State is guided, affects the teaching work, making professional of basic education to pursue, individually, his/her good performance, and leading him/her to become \"entrepreneur of itself.\" Thus, the teacher profile, considering the challenges of the twenty-first century, consists in developing skills, moral and ethical skills combined with the entrepreneurial / innovative / creative spirit, resignifying practices in everyday school life. In the context of contemporary capitalism, the \"productive reengineering of work\" is orchestrated by flexible working; and the entrepreneur figure comes into play under different aspects, gaining space the \"entrepreneur of itself.\" Thus, the work phenomenon and professionalization unveils enterprising feature of the teacher\'s work and the enterprising culture, before present just on the business area, goes to university and, without asking permission, enters the public schools, via economic policy of the Federal Government implementing its educational policy with the Education Development Plan.